Risk assessment for waste water project using public private partnership in Malaysia / Elmi Alif Azmi - Azmi, Elmi Alif (2015)
The waste water project using Public Private Partnership (PPP) encompasses a lot of risks. Most of the previous studies show that although forming the PPP is a promising technique, there are still a lot of PPP/ PFI projects which experienced early termination or re-negotiation due to the lack of managing the risks exposed. Assessment of the risk related to the PPP project needs to be performed in order to evaluate and respond to the risks to manage them adequately. The idea to establish the risk assessment tool for waste water projects using PPP appeared to be a proactive approach in order to achieve the successfiilness to the projects. Therefore, this research is intended to following the aim to form a risk assessment tool. Several objectives for this study have been set up in order to achieve the goal, which identified the related risks to PPP waste water projects; determine the critical risks of PPP waste water projects; determine the mitigation measures; and establish the risk assessment tool for PPP waste water projects. The development of the risk assessment tool resulted from the prospect of the public and private sector views. The risk assessment tool could be valuable for risk management practice for PPP waste water projects in Malaysia. It could make the assessment of the related risks easier and effective in order to manage the risks well and avoid from any losses to the projects. The research then concludes by recommending the application of the risk assessment tool to be implemented in the risk management for PPP waste water projects and the tools could also be used by both the public and private sectors.